Comparação de métodos de conservação sobre os processos fisiológicos e bioquímicos relacionados com características essenciais à qualidade e comercialização do mamão Carica papaya L. - Lopes, Bruna Figueredo (2007)
The papaya is a climateric fruit of difficult handling in the stages between the harvest and the consuming market. During the matureness the polyssacarides of the cell wall, responsible for texture of the fruits, are degraded for hydrolytic enzymes (pectinamethylesterase (PME), polygalacturonase (PG) and cellulase), what causes loss of the texture. This work compared the effect of three conservation methods on the biochemical/physiological processes related to essential characteristics of the quality and commercialization of the Carica papaya L. cv Golden. The fruits were harvested into maturation 1 degree and separate in 3 groups: (C) control - washing in water chlorinated; (TS) treatment standard - type exportation; (I) irradiated - gamma radiation 0,8kGy. The fruits were kept in natural conditions for ripening and the organoleptic characteristics and the activities of enzymes in cell wall were evaluated. The fruits of group I had presented greater texture and minor activity of the PME, ß-gal and celulase, which suggests that the gamma radiation slows the ripening of fruits by reducing the activity of these enzymes. The carbohydrates content was similar for all the groups (11,57± 0,44 g/100g pulp) when these had reached ideal texture for the consumption, 4º, 6º and 10º day postharvest for fruits of groups TP, C and I respectively. These results show that the irradiation gamma was the most efficient treatment among the tested, because it has provided 4 and 6 days of conservation supplied respectively when compared with fruits of groups C and TP, without compromising the sensory and nutritional characteristics.